Solid state diffusion bonding of superalloy X-750 in air ambience - Dong, Guo Ming (2011)
Conventional diffusion bonding processes require a vacuum ambience. This results in high production cost and other disadvantages and limits its application. Therefore, alternative bonding methods have been sought by researchers for a long time. In this study, a novel form of diffusion bonding was proposed that can be carried out in air ambience with an in-situ intervention. The bonding mechanisms and bond properties were subsequently investigated.